Therapeutic drug monitoring in pediatric patients treated with anti-tuberculosis medications by high performance liquid chromatography - OKUYAN, BETÜL; TOK, FATİH; KARAKUŞ, SEVGİ; KAYMAKÇIOĞLU, BEDİA; SANCAR, MESUT (My University, 2022)
© 2022 Marmara University Press.The aim of this study is to perform therapeutic drug monitoring for isoniazid (INH), rifampicin (RIF), and pyrazinamide (PZA) in pediatric tuberculosis patients. The study was carried out in 3 different training-research hospitals in Istanbul, Türkiye between 2011 and 2012. The pediatric patients (aged ≤14 years) who initiated the standard primary anti-tuberculosis therapy were included in this study. The serum samples were collected 3 hours after the first medication doses were given on the 5th day of treatment. Chromatographic experiments were performed on an Agilent 1100 High-Performance Liquid Chromatography (HPLC) system, and the separation was carried out on a Nova-Pak C18 (3.9x150 mm, 5 μm, Merck) analytical column. In this HPLC method, the gradient elusion delivered 3% to 40% (v/v) acetonitrile in phosphate buffer was used, and diode array detector. Twenty-three children (60.9% male) patients were included with a mean age of 111.70 ± 59.94 months. Plasma levels were measured sub-therapeutically for INH in 14, RIF in 10, and PZA in 5 patients, according to the normal range of adult patients. Maximum plasma concentrations after three hours were found between 0.53-14.02 mg/L for INH, 11.17-60.39 mg/L for PZA, 2.15-16.75 mg/L for RIF. In conclusion, this method has been successfully applied to simultaneously determine RIF, INH, and PZA plasma levels in pediatric tuberculosis patients. RIF and INH plasma levels were found to be lower in pediatric patients with tuberculosis compared to target range of adult patients.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); HPLC; pediatric patients; therapeutic drug monitoring; tuberculosis